Long-term disease-free survival following comprehensive involved site radiotherapy for oligometastases - Kao, Johnny; Sahagian, Michelle; Gupta, Vani; Missios, Symeon; Sangal, Ashish (Frontiers in Oncology, 2023)
Introduction Despite recent advances in drug development, durable complete remissions with systemic therapy alone for metastatic cancers remain infrequent. With the development of advanced radiation technologies capable of selectively sparing normal tissues, patients with oligometastases are often amenable to comprehensive involved site radiotherapy with curative intent. This study reports the long-term outcomes and patterns of failure for patients treated with total metastatic ablation often in combination with systemic therapy. Materials and methods Consecutive adult patients with oligometastases from solid tumor malignancy treated by a single high volume radiation oncologist between 2014 and 2021 were retrospectively analyzed. Oligometastases were defined as 5 or fewer metastatic lesions where all sites of active disease are amenable to local treatment. Comprehensive involved site radiotherapy consisted of stereotactic radiotherapy to a median dose of 27 Gy in 3 fractions and intensity modulated radiation therapy to a median dose of 50 Gy in 15 fractions. This study analyzed overall survival, progression-free survival, patterns of failure and toxicity. Results A total of 130 patients with 209 treated distant metastases were treated with a median follow-up of 36 months. The 4-year overall survival, progression-free survival, local control and distant control was 41%, 23%, 86% and 29%. Patterns of failure include 23% alive and free of disease (NED), 52% distant failure only, 9% NED but death from comorbid illness, 7% both local and distant failure, 4% NED but lost to follow-up, 4% referred to hospice before restaging, 1% local only failure, 1% alive with second primary cancer. Late grade 3+ toxicities occurred in 4% of patients, most commonly radionecrosis. Conclusion Involved site radiotherapy to all areas of known disease can safely achieve durable complete remissions in patients with oligometastases treated in the real world setting. Distant failures account for the majority of treatment failures and isolated local failures are exceedingly uncommon. Oligometastases represents a promising setting to investigate novel therapeutics targeting minimal residual disease.